Melhoramento de pimenta calabresa através de introdução sui generis de germoplasma - Ribeiro, Claudia S. C.; Soares, Renato S. [UNESP]; Gomes, Lucas M.; Coelho, Lucas G. F.; Reifschneider, Francisco J. B. (FapUNIFESP (SciELO), 2017)
Few Calabrian pepper cultivars (C. annuum and C. baccatum) are available in the Brazilian market, and among these, only BRS Mari (C. baccatum) was developed in Brazil, by Embrapa. This work aimed to report on the introduction of germplasm in a sui generis way and the initial results of Calabrian pepper breeding at Embrapa Vegetables. Original population was obtained through separation of seeds found in dehydrated Calabrian pepper flakes imported from India. The breeding method was individual selection of plants with progeny test and three generations of selection and self-pollination were advanced. Ten plants were obtained from the original seeds, which were self-pollinated and originated 87 S1 plants. Out of these, seeds of 73 S1 plants were obtained and gave rise to 73 S2 lines. Based on the characteristics of plant and fruit (number of side shoots, weight and total number of fruits, length and width of fruits, wall thickness, color of the ripe fruit, total soluble solids and capsaicin content), three S2 lines were selected and, then, 14 plants within these lines (4 plants of line CNPH 50.112, 5 plants of CNPH 50.116 and 5 plants of CNPH 50.185). Significant differences (Tukey, p<0.05) were noticed among the 14 S3 lines, for precocity, length and width of the fruit, weight of the fruit, weight and number of fruits per plant. Five S3 lines were selected based on the following criteria: average fruit weight above 12 g, early flowering (less than 80 days after sowing), fruit length above 13 cm and fruit width around 1.5 cm, dark green color of leaf and sparse or medium pilosity. In the following S4 generation, the selected lines will be evaluated in order to determine yield, disease resistance as well as capsaicinoid concentration in fruits. New genotypes selected may be released as cultivars that meet the growing demand for dehydrated Calabrian pepper flakes.
Breeding Calabrian pepper lines for Brazilian agriculture from sui generis introduction of germplasm
Keywords: Capsicum annuum; Pepper flakes; Pepperoncino; Selection